Integrating Generative AI into IoT-Based Cloud Computing: Opportunities and Challenges in the United States - Raghuwanshi, Prashis (Journal of Artificial Intelligence General science (JAIGS) ISSN:3006-4023, 2024)
The integration of Generative AI into IoT-based cloud computing offers transformative opportunities while introducing challenges. This paper explores the potential synergies between these technologies to enhance data processing, decision-making, and automation in IoT environments. The research focuses on three objectives: examining the synergies between Generative AI and IoT cloud infrastructures, identifying key technical and ethical challenges (including data privacy, scalability, and energy efficiency), and proposing solutions. Key findings reveal that Generative AI optimizes resource allocation, improves predictive analytics, and enables adaptive IoT networks. However, it also raises concerns about data security and governance. Successful integration will require interdisciplinary collaboration and new regulatory standards to mitigate risks.